2014
DOI: 10.18632/oncotarget.1664
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Pentraxin 3 in bone metastatic breast cancer is correlated with osteolytic function

Abstract: Pentraxin 3 (PTX3), a modulator of tumor-associated inflammation, is known to be positively correlated with tumor grade and severity of malignancies, but its exact role remains unclear. This study found that PTX3 expression was up-regulated in distant bone metastases of breast cancer compared to lung, liver, and brain metastases in 64 human breast cancer patients. Elevated expression of PTX3 was correlated with poor survival in patients with breast cancer. PTX3 expression was also up-regulated in a bone metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 51 publications
2
69
0
Order By: Relevance
“…Here we found that BDNF promoted the secretion of PTX3 from gastric cancer cells in humans (Figure 3) and, in turn, PTX3 induced RANKL secretion from OBs to further amplify OC formation in a co-culture system (Figure 4), thereby mimicking the BM environment [47] and reinforcing the idea that BDNF and PTX3 likely contribute to the bone-destructive process and disease progression in gastric cancer. Our recent study provided further support for a role of PTX3 in osteoclastogenesis by demonstrating a correlation between elevated PTX3 in bone metastatic breast cancer and osteolytic function [39]. Taken together, these results suggest that BDNF is an important factor that contributes to the RANKL pool directly or via PTX3 upregulation in the bone, thereby suggesting that BDNF eventually creates a vicious cycle between OCs and bone metastatic gastric cancer cells to promote the osteolytic process and gastric cancer tumor growth.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Here we found that BDNF promoted the secretion of PTX3 from gastric cancer cells in humans (Figure 3) and, in turn, PTX3 induced RANKL secretion from OBs to further amplify OC formation in a co-culture system (Figure 4), thereby mimicking the BM environment [47] and reinforcing the idea that BDNF and PTX3 likely contribute to the bone-destructive process and disease progression in gastric cancer. Our recent study provided further support for a role of PTX3 in osteoclastogenesis by demonstrating a correlation between elevated PTX3 in bone metastatic breast cancer and osteolytic function [39]. Taken together, these results suggest that BDNF is an important factor that contributes to the RANKL pool directly or via PTX3 upregulation in the bone, thereby suggesting that BDNF eventually creates a vicious cycle between OCs and bone metastatic gastric cancer cells to promote the osteolytic process and gastric cancer tumor growth.…”
Section: Discussionsupporting
confidence: 52%
“…We previously reported that bone metastatic breast cancer cell-derived PTX3 enhanced osteoclastogenesis by upregulating RANKL expression in OBs [39]. Therefore, we reasoned that BDNF-derived PTX3 induction in bone metastatic gastric cancer cells may upregulate RANKL expression in OBs, thereby stimulating OC formation.…”
Section: Resultsmentioning
confidence: 97%
“…On the other hand, injured C / EBPδ −/− mice show reduced glial scarring and improved locomotor recovery. In fact, we have demonstrated previously that activated microglia/macrophages are reduced in the brain of amyloid precursor protein transgenic and C / EBPδ -deficient ( APP Tg/ C / EBPδ −/− ) mice, indicating a relatively mild inflammation in these mice due to the lack of Cepbd compared with the wild-type mice [45]. …”
Section: Discussionmentioning
confidence: 99%
“…C/EBPδ has been suggested to regulate many inflammatory molecules, such as TNF-α, IL-1β, IL-6, CXCL1, IL-17A, MCP-1, PTX3, and COX-2 [45, 46, 54, 55]. In addition to C/EBPδ, activation of transcription factors NF-κB, CREB, and STAT3 in astrocytes has been observed in many neuro-inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…These cells were cultured in keratinocyte serum-free medium (KSFM; Thermo Fisher Scientific, MA USA), supplemented with epidermal growth factor (EGF; 10 ng/ml), bovine pituitary extract (BPE; 40 µg/mL), and antibiotics (100 U/mL penicillin G, 100 mg/mL streptomycin) at 37°C in humidified air with 5% CO 2 . The concentrations of Rh-PTX3 were the same as used previously [15,16].…”
Section: Cell Culturementioning
confidence: 99%